-14+49v=42

Simple and best practice solution for -14+49v=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14+49v=42 equation:


Simplifying
-14 + 49v = 42

Solving
-14 + 49v = 42

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + 49v = 42 + 14

Combine like terms: -14 + 14 = 0
0 + 49v = 42 + 14
49v = 42 + 14

Combine like terms: 42 + 14 = 56
49v = 56

Divide each side by '49'.
v = 1.142857143

Simplifying
v = 1.142857143

See similar equations:

| x^2=-54-15x | | 5/x=55/22 | | .5(8x-43+10)=2x | | 36+16u=52 | | -3(5z-12)= | | -x+179=229 | | 2/3(5x) | | 18x-3=20x-16 | | f(-7)=3y-5 | | 4(x+8)+x=12 | | f(y)=3y-5 | | 10x+20=2x-4 | | (4x-8)/(3)=4 | | 221=8-x | | 21+49x=7 | | 150(x/6) | | 268-w=148 | | 4x-(9x+8)=27 | | 6=6(4q+1) | | h(t)=t^2-3t+5.5 | | 36v+24=48 | | 3r=18(6r+3) | | R(x)=(x-3)/(x-4) | | X-5*4*7=35 | | 5x-y=79 | | (3v-2)-(5-v)=17 | | (2x+3)(3x^2-19x+20)=0 | | 7/3x-5/29 | | -8x-40=7x-12+13x | | m^2+m^3= | | 12/7=5/x | | -x+2=8x-(3x-1) |

Equations solver categories